Scanners - Shore, Howard 1946- (<<The>> Criterion Collection, 2014)
"Ein junger Mann mit todbringenden telepathischen Fähigkeiten, die Nebenwirkung eines Medikaments, das seine Mutter während der Schwangerschaft einnahm, wird von einem Wissenschaftler auf einen ähnlich veranlagten Mann angesetzt, der nach der Weltherrschaft strebt. Mischung aus Horror- und Science-Fiction-Film, der eine Kritik an moderner Medizin und Pharmazeutik anstrebt [...]" [filmdienst.de]
Original: Kanada 1981
director-approved two-DVD special edition features: new, restored 2k digital film transfer, supervised by director David Cronenberg ; "The 'Scanners' way", a new documentary on the films special effects, featuring interviews with Cronenberg's collaborators ; "Mental saboteur", a new interview with actor Michael Ironside; "The Ephemerol diaries", a 2012 interview with actor and artist Stephen Lack ; excerpt from a 1981 interview with Cronenberg on the CBC's "The Bob McLean Show" ; new, restored 2k digital transfer of "Stereo" (1969), Cronenbergs first feature film ; trailer and radio spots ; plus: an essay by critic Kim Newman
Bildformat 1.78:1
Keywords: Film; DVD-Video